2001
DOI: 10.1074/jbc.m104070200
|View full text |Cite
|
Sign up to set email alerts
|

A Second Exon Splicing Silencer within Human Immunodeficiency Virus Type 1 tat Exon 2 Represses Splicing of Tat mRNA and Binds Protein hnRNP H

Abstract: An equilibrium between spliced and unspliced primary transcripts is essential for retrovirus multiplication. This equilibrium is maintained by the presence of inefficient splice sites. The A3 3-splice site of human immunodeficiency virus type I (HIV-1) is required for Tat mRNA production. The infrequent utilization of this splice site has been attributed to the presence of a suboptimal polypyrimidine tract and an exonic splicing silencer (ESS2) in tat exon 2 ϳ60 nucleotides downstream of 3-splice site A3. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
113
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 65 publications
4
113
0
1
Order By: Relevance
“…hnRNP H1 belongs to the superfamily of heterogeneous nuclear ribonucleoproteins (hnRNPs). It binds to intronic oligo-(G) sequences and regulates alternative exons negatively or positively, depending upon the context (Chen et al 1999;Chou et al 1999;Jacquenet et al 2001;Caputi and Zahler 2002;Garneau et al 2005;Crawford and Patton 2006). It was recently shown that hnRNP F and hnRNP H form a complex with RBFOX2, and this interaction enhances hnRNP H/F's ability to antagonize SRSF1 binding to FGFR2 exon IIIc (Mauger et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…hnRNP H1 belongs to the superfamily of heterogeneous nuclear ribonucleoproteins (hnRNPs). It binds to intronic oligo-(G) sequences and regulates alternative exons negatively or positively, depending upon the context (Chen et al 1999;Chou et al 1999;Jacquenet et al 2001;Caputi and Zahler 2002;Garneau et al 2005;Crawford and Patton 2006). It was recently shown that hnRNP F and hnRNP H form a complex with RBFOX2, and this interaction enhances hnRNP H/F's ability to antagonize SRSF1 binding to FGFR2 exon IIIc (Mauger et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids Used in This Study-pLD-C2, pLD-C3, and pLD-L3-U1 constructs, used for production of the C2, C3, and L3-U1 transcripts, were described previously (11,23,24). To build the plasmid pLD-C1, two DNA fragments were generated by PCR amplifications of plasmid pBRU3 (42) containing the HIV-1 BRU/LAI complete cDNA (GenBank TM accession number K02013).…”
Section: Methodsmentioning
confidence: 99%
“…The combination of these various sites gives rise to at least 35 different mRNAs (1). Although the relative efficiencies of the HIV-1 donor sites seem to depend mainly upon their complementarity to the U1 snRNA 5Ј-terminal sequence (3,4), efficiencies of HIV-1 acceptor sites depend upon the presence of cis-regulatory elements (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Several studies have shown that HIV-1 acceptor sites are suboptimal as follows.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the trans-acting factors that bind to these G-tracts belong to the heterogeneous nuclear ribonucleoprotein (hnRNP) F/H family of proteins that consists of five members (hnRNP F, hnRNP H, hnRNP H', hnRNP 2H9, and GRich Sequence Factor (GRSF) 1) 9,10 . GRSF-1 is mainly involved in translation regulation 11,12 and Internal Ribosome Entry Site (IRES) mediated translation 13 , while hnRNP H, H' and F are mostly involved in the regulation of alternative splicing [14][15][16][17][18][19][20][21][22][23] and polyadenylation [24][25][26] . The posttranscriptional regulation by hnRNP F/H proteins is a crucial event since mutations in G-tracts often result in aberrant splicing patterns and can be associated with various diseases [27][28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%